An overview of instruments for assessing and supporting elementary school students' self-regulated learning. (3rd July 2021) - Koivuniemi, Marika; Järvenoja, Hanna; Järvelä, Sanna; Thomas, Valérie
ABSTRACT: This study summarises existing instruments for measuring and supporting self-regulated learning (SRL) in schools using articles from the SCOPUS and Web of Science databases. We analyse how the instruments address cognition, motivation or emotions as a target for regulation and whether they acknowledge the phase of SRL (forethought, performance or reflection) that is used. The results show that the instruments accurately specified the SRL target/s, although the regulation phase was specified only 32.7% of the time. Moreover, the SRL assessment instruments measured students' cognition and motivation, whereas support focused only on cognitive processes. If SRL instruments are intended for future pedagogical use, supports that explicitly target motivation and emotion and acknowledge the differences between SRL phases should be designed.